Arc welding - Safetycare Australia Pty. Ltd.; Skills Education Australia (Australia : Safetycare Australia Pty Ltd., 1989)
A program that shows the safety techniques in handling electic welding and how to avoid being injured during working
Title from title screen
Instructor: Michael Day
Keywords: Electric welding; Welding